MEDICINAL PLANTS OF NORTH-EAST REGION OF INDIA: A SMALL REVIEW - Sharma, Mrinmoy; Das, Biswajit (International Journal of Current Pharmaceutical Research, 2018)
Assam is a state of the North Eastern part of India. There are varieties of plants distributed in various parts of the state. 50% of India's entire plant biodiversity is contributed by the North Eastern States i.e., Manipur, Mizoram, Sikkim, Tripura including Assam. The Ministry of Environment and Forests (MoEF), Government of India in 1980s recorded two hundred and eighty-six (286) species of plants from Assam, used by the tribes of Assam. The traditional system of medicine plays an important role in the healthcare of rural people for all types of ailments. The healing power of traditional herbal medicines has been realized and documented since Rigveda and Atharvaveda. Nearly 80% of the world populations rely on traditional medicines for primary health care, most of which involve the use of plant extracts.